“Art is a way of being in the world”: Use of Art by university teachers - Silva, Silvia Maria Cintra da; Pizzo, Giovanna Malavolta; Stacciarini Jr., Fabiano Prata; Pessoa, Camila Turati (Farol, 2024)
The article reports on research that aimed to understand and analyze the use and enjoyment of Art by teachers at a public University in Minas Gerais. Data construction was carried out through an online questionnaire that covered questions such as the definition of Art; interest and appreciation of artistic languages; function of Art at the University and its use in academic activities. We had 38 teachers respond, mostly from Human Sciences, with unanimous interest in Art. Most of us understand it as a form of expression of feelings and human subjectivity and use it in classroom activities. In general, even with the recognition of the importance of Art, it is still necessary to reiterate its use at the University, aiming for an expanded training of future professionals.